Canal of Nuck incarcerated ovarian hernia in a female infant (Janaki Medical College Journal of Medical Science, 2023)
Background & Objective: Hernia of canal of Nuck is a rare condition, and complications like incarceration and strangulation may occur. We present a rare case of incarcerated ovarian hernia within the canal of Nuck diagnosed timely after ultrasound examination.Presentation of case: A 4-month-old infant girl presented with a left inguinal swelling. On physical examination, there was an oval, non-mobile swelling. Ultrasound examination revealed an incarcerated ovarian hernia with internal doppler flow and immediately sent to surgery department.Discussion: Canal of Nuck is the persistent inguinal processus vaginalis in female. Failure of obliteration of this canal leads to outpouching of intraperitoneal content into this canal. This persistent canal can contain fluid, omentum, fallopian tube, ovary, uterus and even urinary bladder. Ultrasound examination is handy in examining inguinal canal.Conclusion: Awareness of Canal of Nuck hernia is important for differential diagnosis and ultrasound examination for correct diagnosis and complication prevention.